Determinants Of Waqf Interest Through Digital Media In Banda Aceh City - Abdul Jabbar, Caesar; Nirlina, Eka; Sari, Nurma (Risalah Iqtishadiyah, 2025)
This research was conducted to analyze the effect of income, trust, religiosity and social influence on interest in cash waqf through digital media in the Banda Aceh city. The sample used in this study amounted to 100 respondents obtained from the calculation of the slovin formula. This type of research is quantitative research with primary data as a source of data in the research. The results of the study show that partially income, trust, religiosity, and social influence influence interest in waqf in the Banda Aceh city. Simultaneously, income, trust, religiosity and social influence affect interest in waqf through digital media in the Banda Aceh city. To increase interest in digital waqf, people can increase income, trust, religiosity, and social influence. Therefore, the public can take advantage of digital media as a means of cash waqf.